PELATIHAN: PENTINGNYA SOFT SKILL UNTUK KESUKSESAN KERJA BAGI SISWA-SISWI SEKOLAH MENENGAH KEJURUAN - Christine Winstinindah Sandroto (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
Training with the topic "the importance of soft skills in job success for Vocational High School students"  is deemed necessary for preparation in entering the workplace.  Besides hard skills, soft skills also play an essential role in work success. The training is packaged in a talk-show format via Instagram Live, which is considered relevant for Vocational High School students under supervised Bulir Padi. The material covered in this training includes: What are soft skills? The difference between hard skills?; The benefits of having soft skills at work; and how to improve soft skills. This activity in the form of training packaged in a talk show with Instagram Live media is carried out following the preparation and implementation stages. The evaluation stage is not carried out in a structured manner. Still, from the responses and questions that arise, we can conclude that the participants are interested in joining the talk-show enthusiastically. In the next training, if it is still in a covid-19 pandemic situation that does not allow face-to-face meetings at the same location, we will continue to apply training virtually either with the zoom application, google meet, or with Instagram Live. The training evaluation will be made more structured by distributing questionnaires to determine the level of participant satisfaction with the training and conducting pre and post-test materials to determine the progress of participants.